Strategi Pengelolaan dan Pemungutan Retribusi Parkir di Kota Palu - Dicky Yusuf; Rajindra Rajindra (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2019)
Users of parking service sometimes have to experience inconvenience related to parking fees in certain locations due to no longer in line with those set by the parking UPTD. This study aims to find out the strategy of managing and collecting the parking fees. The method used in this research was descriptive method. This research was conducted in South Palu Subdistrict area which was held from April to November 2018. The speakers for this study were 6 people who were selected purposively based on aspects of social life, environment, economy and experience in managing parking fees. This study used a SWOT analysis. The results of the study show that the parking arrangement conditions in Palu City are not neatly organized and the parking management is not optimal, such as the reduced number of roads for parking, the lack of parking space requirements which could lead to congestion on a number of roads at certain hours and retribution not in accordance with the provisions. This research concludes that the implementation of local regulations has not been optimal so that it is necessary to review the existence of local regulations through survey activities tailored to the needs of the community.